Efficacy and safety of ephedra-containing oral medications: a systematic review, meta-analysis, and exploratory dose–response analysis for weight reduction - Cho, Hyeongyu; Oh, Jeewoo; Chu, Hongmin; Jin, Hanbit; Leem, Jungtae (Frontiers in Pharmacology, 2024)
Despite the widespread use of ephedra in various forms, including food supplements and herbal prescriptions, comprehensive studies reviewing efficacy and safety across different countries are lacking. We systematically searched five electronic databases and conducted a meta-analysis of 16 randomized controlled trials (RCTs) on ephedra-containing oral medications (EOM), performing a dose-response analysis for weight loss. The meta-analysis results revealed a statistically significant reduction in body mass index (BMI) (MD 1.5 kg/m2, 95% CI -2.46 to -0.54) and secondary outcomes like body weight (BW) and waist circumference (WC). Dose-response analysis indicated a correlation between ephedra and weight reduction. Safety analysis showed no significant difference in adverse effects between the treatment and control groups (RR=0.99, 95% CI=0.80 1.21, P=0.90). In conclusion, EOM has demonstrated effectiveness in promoting weight loss, and the dose-response analysis indicated a correlation between ephedra and weight reduction. However, additional research is necessary due to the limited number of studies and inconsistent results among the assessment criteria. Moreover, if prescribed by traditional medicine physicians within the permissible daily ephedrine dosage range of 150 mg set by the Food and Drug Administration and monitored by healthcare professionals, the risk of severe adverse events is likely minimal.